Implementation of Tracing System for Covid-19: A Literature Review - Dwi Yulianingsih Putri Hanardi; Erna Rochmawati (Universitas Aisyah Pringsewu, 2022)
COVID19 virus spreads very fast and can result in death. COVID19 incident has also impacted all sectors of life. Governments in many countries made various efforts to control the rate of transmission including developing and implementing contact tracing for COVID19. Contact tracing or tracing systems is a priority effort Contact tracing or tracing systems is a priority effort to contain the spread of the coronavirus and reduce mortality due to covid19. This paper aims to analyze the implementation covid-19 tracing system as an effort to restrain the covid-19 outbreak. The following bibliographic databases were searched to identify potentially relevant documents: SCOPUS, EBSCOHost, EMERALD, ScienceDirect, and PubMed. The search strategy was developed by the first author and further refined through team discussions. The final search results are exported to EndNote, and duplicates are removed automatically and manually. Then for the report format, follow PRISMA. 12 articles were included in the review. We found several things in analyzing the implementation of contact tracing such as the impact of implementing contact tracing, contact tracing management, and obstacles to implementing contact tracing in controlling covid19 outbreak. Contact tracing or tracing systems have a positive impact on reducing and controlling the transmission and spread of the COVID19 disease. Abstrak: Virus COVID19 menyebar sangat cepat dan dapat mengakibatkan kematian. Wabah COVID19 juga berdampak pada semua sektor kehidupan. Pemerintah di banyak negara melakukan berbagai upaya untuk mengendalikan laju penularan termasuk mengembangkan dan menerapkan pelacakan kontak COVID19. Pelacakan kontak atau sistem pelacakan merupakan upaya prioritas menahan laju penularan virus corona dan mengurangi angka kematian akibat covid-19. Makalah ini bertujuan untuk menganalisis penerapan sistem pelacakan covid19 sebagai upaya pengendalian wabah covid-19. Basis data bibliografi berikut dicari untuk mengidentifikasi dokumen relevan yang potensial: SCOPUS, EBSCOHost, EMERALD, ScienceDirect, dan PubMed. Strategi pencarian dikembangkan oleh penulis pertama dan disempurnakan lebih lanjut melalui diskusi tim. Hasil pencarian akhir diekspor ke End Note, dan duplikatnya dihapus secara otomatis dan manual. Kemudian untuk format laporan, mengikuti PRISMA. 12 artikel dimasukkan dalam review. Kami menemukan beberapa hal dalam menganalisa pelaksanaan contact tracing seperti dampak penerapan pelcakan kontak, manajemen pelcakan kontak, dan kendala penerapan pelcakan kontak dalam pengendalian wabah covid19. Pelacakan kontak atau sistem pelacakan berdampak positif dalam mengurangi dan mengendalikan penularan dan penyebaran penyakit COVID19.